Ethical Views on Sharing Digital Data for Public Health Surveillance: Analysis of Survey Data Among Patients - Garett, Renee; Young, Sean D. (Frontiers in Big Data, 2022)
Digital data, including social media and internet search data, are increasingly being integrated into public health research. Because of the current issues around public distrust of science, it is essential that researchers conduct ongoing studies assessing people’s perceptions around and willingness to share digital data. This study aims to examine participants’ social media use and comfort sharing their data with health researchers. One hundred and sixty-one participants with medical conditions were recruited through social media paid advertisements and referral from a website, and invited to complete surveys on social media use and ethical perspectives on data sharing. Eligibility criteria were adults 18 years old or older, living in the US, self-reported having been diagnosed by a physician with a medical condition, belonging to at least one social media platform, using social media at least twice a week, and owning a smartphone. Study participants were mostly female, White, and with a mean age of 36.31 years. More than one third of participants reported being very comfortable sharing electronic health data and social media data for personalized healthcare and to help others. Findings suggest that participants are very uncomfortable sharing their location and text message data with researchers, with primary concerns centered around loss of privacy, disclosing private information, and that friends, family, and others may find out that they shared text messages with researchers. We discuss the implications of this research before and after the COVID-19 pandemic, along with its potential implications for future collection of digital data for public health.